Studies in Romance Lexicology, Based on a Collection of Late Latin Documents from Ravenna (A.D. 445-700) - Carlton, Charles Merritt (Book collections on Project MUSE., 1965)
Charles Merritt Carlton studies in detail some forty words that he has found in the texts published by Tjader in hisDie nichtliterarischen lateinischen Papyri Italiens aus der Zeit 445-700, vol. I (Lund, 1955).